Fluorophore‐Labeled Cyclooxygenase‐2 Inhibitors for the Imaging of Cyclooxygenase‐2 Overexpression in Cancer: Synthesis and Biological Studies. Issue 1 (31st October 2013) - Bhardwaj, Atul; Kaur, Jatinder; Wuest, Frank; Knaus, Edward E.
Abstract A group of cyclooxygenase‐2 (COX‐2)‐specific fluorescent cancer biomarkers were synthesized by linking the anti‐inflammatory drugs ibuprofen, (S)‐naproxen, and celecoxib to the 7‐nitrobenzofurazan (NBD) fluorophore. In vitro COX‐1/COX‐2 inhibition studies indicated that all of these fluorescent conjugates are COX‐2 inhibitors (IC50 range: 0.19–23.0 μM) with an appreciable COX‐2 selectivity index (SI≥4.3–444). In this study the celecoxib–NBD conjugate N‐(2‐((7‐nitrobenzo[c][1, 2, 5]oxadiazol‐4‐yl)amino)ethyl)‐4‐(5‐(p‐tolyl)‐3‐(trifluoromethyl)‐1H‐pyrazol‐1‐yl)benzenesulfonamide (14), which displayed the highest COX‐2 inhibitory potency and selectivity (COX‐2 IC50=0.19 μM; SI=443.6), was identified as an impending COX‐2‐specific biomarker for the fluorescence imaging of cancer using a COX‐2‐expressing human colon cancer cell line (HCA‐7).